Research on the Image-Based Life of Elderly Through Art Therapy - Ni, Ziwen; Hu, Xinyue (International Journal of Social Sciences and Public Administration, 2025)
This paper discusses the impact of video art on the improvement of the quality of life of the elderly in their later years, on their sense of well-being and mental health, and then on the formation of an Art therapy effect. With the development of digital technology and smartphones, video has become an important part of the daily life of the elderly, enriching their daily life and becoming a form of enhancing the quality of life and happiness of the elderly, and the Art therapy effect it brings has attracted widespread attention. Starting from the theoretical basis of image creation and dissemination and Art therapy, this paper analyzes in detail the content of the image life of the elderly, the dilemmas faced by the elderly in the digital era, the methods of solving them, as well as the role of Art therapy brought about and its practical approach to be studied.